Penerapan Zonasi Vastu Citra Pada Perancangan Pusat Kesenian Wayang Tradisional Di Bali - Tegar Septian Mboro; Imanuel N. Mbake; I Gusti Ngurah Wiras Hardy (Jurnal Arsitektur ARCADE, 2025)
Abstract:Traditional Balinese wayang, as a cultural heritage, faces the threat of extinction due to digitalization. This research proposes the design of a Wayang Arts Center in Pantai Lembang, Gianyar, as a medium for preserving the artistic meaning through an architectural metaphor approach, utilizing the natural beach lighting as a visual manifestation of "Suryangkara." The methodology begins with field observation, case studies, and secondary data analysis to identify design needs. Based on these findings, the design concept integrates three core principles: Transfer of Illumination, which transforms the philosophy of the cakra into the Vastu Citra structure; Subjective Perception, which creates a dual-stage interpreted as either Kayon (tree of life) or Ajna Chakra (eye of wisdom) depending on the viewer’s perspective; and Hybridization through QR codes embedded in cultural artifacts. This approach is synthesized with Vastu Citra zoning based on Nawa Sanga, linking deity-chakra associations and prana flows, and placing an open stage at the Brahmasthan as a cosmic axis. The result is a symbolic building serving as a space for the "rebirth" of wayang, where the integration of metaphor and Vastu Citra creates a functional space that also acts as a medium for cultural storytelling. The implication offers a locally rooted and adaptive design model for preserving traditional arts in the digital era. Keyword: Balinese wayang, metaphorical architecture, Vastu Citra, arts center, Suryangkara, chakra.  Abstrak: Wayang tradisional Bali sebagai warisan budaya menghadapi tantangan kepunahan akibat digitalisasi. Penelitian ini merancang Pusat Kesenian Wayang di Pantai Lembang, Gianyar, sebagai sarana pelestarian makna seni melalui pendekatan metafora arsitektur dengan memanfaatkan pencahayaan alami pantai sebagai manifestasi visual "Suryangkara". Metode diawali observasi lapangan, studi kasus, dan analisis data sekunder untuk mengidentifikasi kebutuhan desain. Berdasarkan temuan tersebut, konsep desain mengintegrasikan tiga prinsip kunci: (1) Transfer Keterangan mentransformasikan filosofi cakra ke dalam struktur Vastu Citra; (2) Persepsi Subjektif menciptakan panggung ganda yang dibaca sebagai Kayon (pohon kehidupan) atau Cakra Ajna (mata kebijaksanaan) bergantung perspektif pengamat; (3) Hibriditas melalui QR code pada artefak budaya. Pendekatan ini disinergikan dengan zonasi Vastu Citra berbasis Nawa Sanga yang menghubungkan asosiasi dewa-cakra dan aliran prana, serta menempatkan open stage di Brahmasthan sebagai poros kosmis. Hasilnya adalah bangunan simbolis sebagai ruang "kelahiran kembali" wayang, di mana integrasi metafora-Vastu Citra menciptakan ruang fungsional sekaligus medium narasi budaya. Implikasinya menawarkan model desain berbasis kearifan lokal yang adaptif untuk pelestarian kesenian tradisional di era digital Kata Kunci: wayang Bali, Metafora Arsitektur, Vastu Citra, Pusat Kesenian,  Suryangkara, cakra.